2018
DOI: 10.1177/205016841800700408
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Interventions for Persistent Orofacial Pain

Abstract: Persistent pain has been defined as pain lasting beyond the normal time of healing (up to six months), often in the absence of observable tissue pathology. It includes a range of conditions which are likely to present in the dental setting including temporomandibular disorders, burning mouth syndrome, persistent dentoalveolar pain, trigeminal nerve injury, trigeminal neuralgia and atypical facial pain. This article reviews psychological interventions for pain. This includes interventions that have been resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A Cochrane review says that PMPS is more effective than regular care and physical therapy for treating pain and disability. Outcomes can be maintained for at least 12 months post-treatment [ 26 ].…”
Section: A Stepped Care Approach For the Cliniciansmentioning
confidence: 99%
“…A Cochrane review says that PMPS is more effective than regular care and physical therapy for treating pain and disability. Outcomes can be maintained for at least 12 months post-treatment [ 26 ].…”
Section: A Stepped Care Approach For the Cliniciansmentioning
confidence: 99%
“…This protocol is less well understood, but also shows early promise in reducing pain catastrophization. 3 Thus, the treatment of facial pain should be managed by a multidisciplinary / interdisciplinary team that seeks to develop a therapeutic plan aimed at reducing crises and pain symptoms, as well as maintaining patient autonomy and quality of life. This means avoiding iatrogenic procedures, which, without positive results, ultimately cause discomfort and suffering in the patient, contributing to delayed identification and poor prognosis in the development of facial pain.…”
Section: Opinionmentioning
confidence: 99%
“…Its main long-term consequence is the formation of a behavioral repertoire, depleted and supported by aversive stimuli (consistent attempts to control and avoid pain in the form of constant wearing of a mouth guard, applying cold to the face, constant treatment of dentists) and the growth of avoidant behavior. 2,3 Orofacial pain is multifactorial, and along with the pathology in the dental clinic, we mental health professionals need to take into account psychological factors.…”
mentioning
confidence: 99%
“…Psychosocial therapy in the treatment of chronic pain conditions has advantages owing to non‐invasive nature of intervention. These treatments do not aim to remove the pain, but rather improve a patient's management of the pain and attempt to reduce the resultant impact upon quality of life which follows. Unfortunately, there are no specific data on the efficacy of psychosocial management for PIDP and a Cochrane review on its use in orofacial pain supported its use, but concluded that the evidence was weak.…”
Section: Impactmentioning
confidence: 99%